Substrate recognition by holocytochrome c synthase in cytochrome c biogenesis system III - Zhang, Y (2015)
C-type cytochromes are ubiquitous proteins with crucial functions in organisms, which include electron transfer and apoptotic signalling. In eukaryotic organisms, mitochondrial cytochrome c is located in the intermembrane space, and it is a component of the electron transport chain; it is responsible for transferring electrons from Complex III to Complex IV. The regulated release of cytochrome c from mitochondria results in the activation of a signal transduction pathway leading to controlled cell death, or apoptosis. In mitochondrial c-type cytochromes, the heme is bound to both cysteines of a CXXCH motif located near the N-terminus. The covalent heme attachment in c-type cytochromes, the final step in its biosynthesis, is achieved by different cytochrome c biogenesis systems in different organisms. Out of these systems, System III, found in many eukaryotes, has a single component - holocytochrome c synthase (HCCS) which is the enzyme responsible for the catalysis of heme binding to cytochrome c. HCCS recognises apocytochrome c as a substrate upon the import of the apocytochrome from the cytosolic space to the mitochondrial intermembrane space. The requirements of amino acid sequence for HCCS recognition had remained an intriguing question, despite the relatively long period since the discovery of the enzyme. Thus, HCCS in System III and its substrate recognition is the subject of this thesis. This thesis describes the experiments showing that the N-terminal region of the mitochondrial cytochrome c protein is important for substrate recognition, as well as further characterisation of this sequence by mutagenesis. Out of several highly conserved residues in the N-terminus, a phenylalanine residue in the N-terminus is identified to be critical for heme attachment by HCCS. The role of this phenylalanine residue in the interaction between the two proteins was probed by substituting it with a range of residues. Furthermore, the importance of the spacing between the key phenylalanine residue and the CXXCH motif was investigated. A single-cysteine variant of the mitochondrial cytochrome c with a single bond to the heme is produced by HCCS, but heme attachment only occurs if histidine is present as an axial ligand to the heme iron. Replacement of the histidine with other potential iron-ligating residues abolished heme attachment. These results bring insight into the critical features in amino acid sequence of cytochrome c for the substrate recognition specificity of HCCS. Sequence analysis on the N-terminal region of mitochondrial cytochromes c in a variety of organisms reveals evolutionary implications for cytochrome c biogenesis systems. It also attempts to explain the reason for negative results in previous chapters for the analysis of the N-terminal region of cytochrome c. An improved method for human HCCS production is also described in this thesis, for the exploitation of purification and characterisation in future studies of HCCS.